Processing and Characterization of Recombinant von Willebrand Factor Expressed in Different Cell Types Using a Vaccinia Virus Vector - Meulien, P; Nishino, M; Mazurier, C; Dott, K; Piétu, G; Jorieux, S; Pavirani, A; Girma, J P; Oufkir, D; Courtney, M; Meyer, D (Thrombosis and Haemostasis, 1992)
The cloning of the cDNA encoding von Willebrand factor (vWF) has revealed that it is synthesized as a large precursor (pre-pro-vWF) molecule and it is now clear that the prosequence or vWAgll is responsible for the intracellular multimerization of vWF. We have cloned the complete vWF cDNA and expressed it using a recombinant vaccinia virus as vector. We have characterized the structure and function of the recombinant vWF (rvWF) secreted from five different cell types: baby hamster kidney (BHK), Chinese hamster ovary (CHO), human fibroblasts (143B), mouse fibroblasts (L) and primary embryonic chicken cells. Forty-eight hours after infection, the quantity of vWF antigen found in the cell supernatant varied from 3 to 12 U/dl depending on the cell type. By SDS-agarose gel electrophoresis, the percentage of high molecular weight forms of vWF varied from 39 to 49% relative to normal plasma for BHK, CHO, 143B and chicken cells but was less than 10% for L cells. In all cell types, the two anodic subbands of each multimer were missing. The two cathodic subbands were easily detected only in BHK and L cells. By SDS-PAGE of reduced samples, pro-vWF was present in similar quantity to the fully processed vWF subunit in L cells, present in moderate amounts in BHK and CHO and in very low amounts in 143B and chicken cells. rvWF from all cells bound to collagen and to platelets in the presence of ristocetin, the latter showing a high correlation between binding efficiency and degree of multimerization. rvWF from all cells was also shown to bind to purified FVIII and in this case binding appeared to be independent of the degree of multimerization. We conclude that whereas vWF is naturally synthesized only by endothelial cells and megakaryocytes, it can be expressed in a biologically active form from various other cell types.